CD36 enrichment in HER2-positive mesenchymal stem cells drives therapy refractoriness in breast cancer - Lorenzo Castagnoli; Alma Franceschini; Valeria Cancila; Matteo Dugo; Martina Bigliardi; Claudia Chiodoni; Paolo Toneguzzo; Viola Regondi; Paola A. Corsetto; Filippo Pietrantonio; Serena Mazzucchelli; Fabio Corsi; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Growing evidence shows that the reprogramming of fatty acid (FA) metabolism plays a key role in HER2-positive (HER2 +) breast cancer (BC) aggressiveness, therapy resistance and cancer stemness. In particular, HER2 + BC has been defined as a "lipogenic disease" due to the functional and bi-directional crosstalk occurring between HER2-mediated oncogenic signaling and FA biosynthesis via FA synthase activity. In this context, the functional role exerted by the reprogramming of CD36-mediated FA uptake in HER2 + BC poor prognosis and therapy resistance remains unclear. In this study, we aimed to elucidate whether enhanced CD36 in mesenchymal HER2 + cancer stem cells (CSCs) is directly involved in anti-HER2 treatment refractoriness in HER2 + BC and to design future metabolism-based approaches targeting both FA reprogramming and the “root” of cancer. Methods Molecular, biological and functional characterization of CD36-mediated FA uptake was investigated in HER2 + BC patients, cell lines, epithelial and mesenchymal CSCs. Cell proliferation was analyzed by SRB assay upon treatment with lapatinib, CD36 inhibitor, or Wnt antagonist/agonist. Engineered cell models were generated via lentivirus infection and transient silencing. CSC-like properties and tumorigenesis of HER2 + BC cells with or without CD36 depletion were examined by mammosphere forming efficiency assay, flow cytometry, cell sorting, ALDH activity assay and xenograft mouse model. FA uptake was examined by flow cytometry with FA BODIPY FL C16. Intratumor expression of CSC subsets was evaluated via multiplex immunostaining and immunolocalization analysis. Results Molecular data demonstrated that CD36 is significantly upmodulated on treatment in therapy resistant HER2 + BC patients and its expression levels in BC cells is correlated with FA uptake. We provided evidence of a consistent enrichment of CD36 in HER2 + epithelial-mesenchymal transition (EMT)-like CSCs from all tested resistant cell models that mechanistically occurs via Wnt signaling pathway activation. Consistently, both in vitro and in vivo dual blockade of CD36 and HER2 increased the anti-CSC efficacy of anti-HER2 drugs favoring the transition of the therapy resistant mesenchymal CSCs into therapy-sensitive mesenchymal-epithelial transition (MET)-like epithelial state. In addition, expression of CD36 in intratumor HER2 + mesenchymal CSCs is significantly associated with resistance to trastuzumab in HER2 + BC patients. Conclusions These results support the metabolo-oncogenic nature of CD36-mediated FA uptake in HER2 + therapy-refractory BC. Our study provides evidence that targeting CD36 might be an effective metabolic therapeutic strategy in the treatment of this malignancy.